Lived experiences of palliative care among people living with HIV/AIDS: a qualitative study from Bihar, India. Issue 10 (5th October 2020) - Nair, Mohit; Kumar, Pragya; Mahajan, Raman; Harshana, Amit; Richardson, Kathryn; Moreto-Planas, Laura; Burza, Sakib
Abstract : Objectives: This study aimed to assess the lived experiences of palliative care among critically unwell people living with HIV/AIDS (PLHA), caregivers and relatives of deceased patients. It also aimed to understand the broader palliative care context in Bihar. Design: This was an exploratory, qualitative study which used thematic analysis of semistructured, in-depth interviews as well as a focus group discussion. Setting: All interviews took place in a secondary care hospital in Patna, Bihar which provides holistic care to critically unwell PLHA. Participants: We purposively selected 29 participants: 10 critically unwell PLHA, 5 caregivers of hospitalised patients, 7 relatives of deceased patients who were treated in the secondary care hospital and 7 key informants from community-based organisations. Results: Critically ill PLHA emphasised the need for psychosocial counselling and opportunities for social interaction in the ward, as well as a preference for components of home-based palliative care, even though they were unfamiliar with actual terms such as 'palliative care' and 'end-of-life care'. Critically unwell PLHA generally expressed preference for separate, private inpatient areas for end-of-life care. Relatives of deceased patients stated that witnessing patients' deaths caused trauma for other PLHA. Caregivers and relatives of deceased patients felt there was inadequate time and space for grieving in the hospital. While both critically ill PLHA and relatives wished that poor prognosis be transparently disclosed to family members, many felt it should not be disclosed to the dying patients themselves. Conclusions: Despite expected high inpatient fatality rates, PLHA in Bihar lack access to palliative care services. PLHA receiving end-of-life care in hospitals should have a separate dedicated area, with adequate psychosocial counselling and activities to prevent social isolation. Healthcare providers should make concerted efforts to inquire, understand and adapt their messaging on prognosis and end-of-life care based on patients' preferences.